PENATAAN REGULASI LEMBAGA NEGARA MANDIRI DALAM STRUKTUR SISTEM KETATANEGARAAN INDONESIA - Ambarwati, Herika; Artina, Dessy; Tiaraputri, Adi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The establishment of an independent state institution has different names, making it unclear in its accountability, through the third amendment to the 1945 Constitution of the Republic of Indonesia it was agreed that the formation of a Judicial Commission based on Article 24B Judicial Commission is independent, this does not give meaningful meaning to its institutional status , The Judicial Commission is clearly closer to the function of judicial power, because the Judicial Commission (KY) regulation is in the 1945 Constitution of the Republic of Indonesia (UUD NRI). In addition, there are also institutions that are at the same level as the Judicial Commission, namely state institutions. independent which has the same level of function. Unlike the Judicial Commission, these three institutions are not regulated in the constitution, namely the Attorney General's Office, the Corruption Eradication Commission, and the National Human Rights Commission. However, the regulation stipulated by article 24 paragraph (3) which states